Discriminatory auction design for renewable energy - Mats Kröger; Karsten Neuhoff; Jörn C. Richstein (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
We assess the incorporation of wind or solar resource quality into renewable auction design as a means to geographically diversify renewable energy production and to reduce costs to consumers by reducing scarcity rents at sites with high resource quality. With a stylized auction model, we model the trade-off between production costs and consumer costs. After exploring the influence of the heterogeneity of production costs, the auction volume, and the regulator's knowledge about cost structures, we show that an optimal level of differentiation exists. Through a numerical analysis of the German reference yield model, we estimate that at current auction levels resource differentiation through the reference yield model leads to a reduction of consumer costs of around 21 billion Euro or 11% between 2025 and 2030, even without considering additional savings from increased regional diversification to reduce grid costs.
Keywords: D44; Q42; Q48; Q54; 330; auctions; renewable energy; price discrimination; resource differentiation; consumer costs